Tentative assessment of the awareness of HIV and AIDS-related issues among stu dents of Nursing Faculty - Symon, Agata; Gotlib, Joanna (Nursing in the 21st Century, 2013)
TENTATIVE ASSESSMENT OF THE AWARENESS OF HIV AND AIDS-RELATED ISSUES AMONG STU DENTS OF NURSING FACULTYIntroduction. Nurses play the most important role in the education of HIV -positive and AIDS sufferers since they work directly with patients and their families in the hospital, at their places of residence and also in the work and/or school setting.Aim. The aim of this study was to assess Nursing students’ awareness of HIV- and AIDS-related issues.Material and methods. Six –hundred and twenty students of the 1st and 2nd year of the MA programme in Nursing: 94% females, 6% males. Mean age: 37.5 years (SD: 3.27, min. 21, max. 39). All the respondents were employed as nurses. Anonymous voluntaryquestionnaire designed by the authors. The results were presented as descriptive statistics. Subgroups were not compared with regard to any factor and a comparative analysis of the findings is deliberately not included.Results. Seventy-six per cent report having worked with HIV-infected individuals, while 54% declare that they would rather avoid infected individuals. Sixty-four percent are anxious while performing procedures in HIV-infected patients. Ninety-eight per cent of the students believedthat it is the nurse who should be responsible for educating HIV-positive patients and AIDS sufferers. Twenty-one percent of the students declared that their level of awareness of HIV and AIDS was sufficient to enable them to educate patients.Conclusions.• The respondents displayed satisfactory general awareness of HIV/AIDS, but their specific knowledge was definitely insufficient, especially considering that they work as nurses and so should be prepared to educate the public about health promotion issues. • The students did not consider themselves well prepared to educate others about HIV/AIDS. Study programs for students of nursing should therefore be modified to include specific HIV/AIDS-related content and instruction on how to convey this content, to prepare students to act as educators.